Rearing of lambs under different grazing methods on annual ryegrass in succession to crops - Macari, Stefani; Carvalho, Paulo César de Faccio; de Oliveira, Lisandre; Devincenzi, Thais; Albuquerque, Caetano; de Moraes, Aníbal (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the rearing of lambs grazing on annual ryegrass (Lolium multiflorum) in succession with corn or soybean crops, managed at moderate or low grazing intensities, with rotational or continuous grazing methods. The experimental design used was randomized blocks in a factorial arrangement 2 intensities x 2 grazing methods, with four replicates. There was no interaction between grazing intensities and methods. Low grazing intensity provided higher forage mass and sward height. Height and forage mass were higher in rotational grazing. There was no difference in average daily gain. There was significant difference in stocking rate for the rotational method and moderate grazing intensity. Gain per hectare was higher for moderate grazing intensity. Grazing intensity and grazing methods did not affect soybean or corn yields in succession. The forage available is the main determinant of yield of the integrated system, independently of the grazing method.